Association of central blood pressure with an exaggerated blood pressure response to exercise among elite athletes - Most, Astrid; Kraushaar, Lutz; Dörr, Oliver; Keranov, Stanislav; Hoelscher, Sophie; Weber, Rebecca; Akdogan, Ebru; Groesser, Vincent; Husain-Syed, Faeq; Nef, Holger; Hamm, Christian W.; Bauer, Pascal; et al. (My University, 2024)
Purpose: The systolic blood pressure/workload (SBP/MET) slope was recently reported to be a reliable parameter to identify an exaggerated blood pressure response (eBPR) in the normal population and in athletes. However, it is unclear whether an eBPR correlates with central blood pressure (CBP) and vascular function in elite athletes. Methods: We examined 618 healthy male elite athletes (age 25.8 ± 5.1 years) of mixed sports with a standardized maximum exercise test. CBP and vascular function were measured non-invasively with a validated oscillometric device. The SBP/MET slope was calculated and the threshold for an eBPR was set at > 6.2 mmHg/MET. Two groups were defined according to ≤ 6.2 and > 6.2 mmHg/MET, and associations of CBP and vascular function with the SBP/MET slope were compared for each group. Results: Athletes with an eBPR (n = 180, 29%) displayed a significantly higher systolic CBP (102.9 ± 7.5 vs. 100 ± 7.7 mmHg, p = 0.001) but a lower absolute (295 ± 58 vs. 384 ± 68 W, p < 0.001) and relative workload (3.14 ± 0.54 vs. 4.27 ± 1.1 W/kg, p < 0.001) compared with athletes with a normal SBP/MET slope (n = 438, 71%). Systolic CBP was positively associated with the SBP/MET slope (r = 0.243, p < 0.001). In multiple logistic regression analyses, systolic CBP (odds ratio [OR] 1.099, 95% confidence interval [CI] 1.045–1.155, p < 0.001) and left atrial volume index (LAVI) (OR 1.282, CI 1.095–1.501, p = 0.002) were independent predictors of an eBPR. Conclusion: Systolic CBP and LAVI were independent predictors of an eBPR. An eBPR was further associated with a lower performance level, highlighting the influence of vascular function on the BPR and performance of male elite athletes.
Keywords: ddc:610